Change in US state-level public opinion about climate change: 2008–2020. (1st December 2022) - Marlon, Jennifer R; Wang, Xinran; Bergquist, Parrish; Howe, Peter D; Leiserowitz, Anthony; Maibach, Edward; Mildenberger, Matto; Rosenthal, Seth
Abstract: Public attitudes toward climate change influence climate and energy policies and guide individual mitigation and adaptation behaviors. Over the last decade, as scientific certainty about the causes and impacts of, and solutions to the climate crisis has increased, cities, states, and regions in the United States have pursued diverse policy strategies. Yet, our understanding of how Americans' climate views are changing remains largely limited to national trends. Here we use a large US survey dataset ( N = 27 075 ) to estimate dynamic, state-level changes in 16 climate change beliefs, risk perceptions, and policy preferences over 13 years (2008–2020). We find increases in global warming issue importance and perceived harm in every state. Policy support, however, increased in more liberal states like California and New York, but remained stable elsewhere. Year-by-year estimates of state-level climate opinions can be used to support sub-national mitigation and adaptation efforts that depend on public support and engagement.